2007
DOI: 10.1021/ja0706246
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptors Self-Assemble in Dynamics Simulations of Model Bilayers

Abstract: Many integral membrane proteins assemble to form oligomeric structures in biological membranes. In particular, seven-transmembrane helical G protein-coupled receptors (GPCRs) appear to self-assemble constitutively in membranes, but the mechanism and physiological role of this assembly are unknown. We developed and employed coarse-grain molecular dynamics (CGMD) models to investigate the molecular basis of how the physicochemical properties of the phospholipid bilayer membrane affect self-assembly of visual rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
363
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(392 citation statements)
references
References 55 publications
28
363
0
1
Order By: Relevance
“…The directionality of bilayer thickness-mediated protein interactions implied by the observed protein structures presents one possible physical mechanism for membrane protein organization and collective function. Such directional interactions can yield [46,47,89,97] ordering of integral membrane proteins, which is also consistent with molecular dynamics simulations [84,95,125,126]. The combined analytic and numerical framework we have discussed here allows calculation of the lipid bilayer-mediated protein interactions implied by bilayer elasticity theory [32][33][34][35][36][37][38][39][40][41][42][43] for the protein shapes suggested by structural studies at arbitrary protein separations and orientations.…”
Section: Discussionsupporting
confidence: 74%
“…The directionality of bilayer thickness-mediated protein interactions implied by the observed protein structures presents one possible physical mechanism for membrane protein organization and collective function. Such directional interactions can yield [46,47,89,97] ordering of integral membrane proteins, which is also consistent with molecular dynamics simulations [84,95,125,126]. The combined analytic and numerical framework we have discussed here allows calculation of the lipid bilayer-mediated protein interactions implied by bilayer elasticity theory [32][33][34][35][36][37][38][39][40][41][42][43] for the protein shapes suggested by structural studies at arbitrary protein separations and orientations.…”
Section: Discussionsupporting
confidence: 74%
“…Consequently, if the protein's hydrophobic part exceeds the bilayer thickness, oligomerization might reduce the exposed hydrophobic area of the protein (Killian, 1998). Using computational methods, this process was analyzed with reference to the association of rhodopsin (Periole et al, 2007) and of the β 1 -and β 2 -adrenergic receptors (Mondal et al, 2013). Interestingly, it was observed that the protein domains most frequently involved in RRIs were also those showing the highest hydrophobic mismatch in monomers, which was substantially alleviated in oligomers.…”
Section: Influence Of the Lipid Environmentmentioning
confidence: 99%
“…6B, Top and Middle Rows). Thus, the H1/H8 domains rather than the H4/H5 domains may be the primary protomer-protomer interface in R/R-opsin and R/S-opsin dimerization during biosynthesis and targeting, although secondary interactions in the H4/H5 domains and even others are still possible in the ROS (33)(34)(35)(36). This result is consistent with the cross-linking experiment involving BM(PEG) 3 and MTS-O5-MTS, whose extended S-S distance of 2.1 and 2.6 nm, respectively, is within the predicted C316-C316 distance of 2.1-2.9 nm in the rhodopsin H1/H8 dimer (2.4 nm in the R/S-opsin heterodimer) (Fig.…”
Section: Disruption By Helix Peptides Of R-and S-opsin Trafficking Inmentioning
confidence: 99%